Does Interactivity in an English Presentation Affect its Preparation Process? - Fumiya Shinozaki; Hiroaki Aoki (Vision: Journal for Language and Foreign Language Learning, 2023)
The purpose of this study is to clarify the differences in the process of students’ preparation and practice outside of class for a one-way or interactive English presentation. The participants were 105 third-year junior high school students in Japan. They were supposed to record their actions while preparing for each type of presentation outside of class for a week. A hierarchical cluster analysis was conducted on all learners based on a self-evaluation questionnaire administered beforehand. Three clusters were created from the dendrogram. Kruskal-Wallis test and multiple comparisons showed significant differences among all items. Each cluster was named "Self-rating (high)", "Self-rating (medium)", and "Self-rating (low)". These three groups were analyzed based on the records and the post-questionnaire. The results indicated that the amount of practice on the day of the presentation was greater for a one-way presentation in any group, while in an interactive presentation, the tendency of the group to “Self-rating (high)” was different from the others. The inclusion of interaction with listeners in a presentation confirmed motivation for further preparation, such as conducting research and creating additional questions and quizzes in advance, suggesting the possibility of a different range of effects on learning.